Plastic pollution solutions: emerging technologies to prevent and collect marine plastic pollution. (November 2020) - Schmaltz, Emma; Melvin, Emily C.; Diana, Zoie; Gunady, Ella F.; Rittschof, Daniel; Somarelli, Jason A.; Virdin, John; Dunphy-Daly, Meagan M.
Highlights: Technology can be used to target hotspots of marine plastic pollution. The Inventory is a tool to identify plastic pollution prevention and cleanup technologies. Fifty-two inventions focus on preventing plastic leakage or collecting marine plastics. Technology alone cannot solve the plastics pollution issue. The Inventory underscores the importance of cross-sector collaborations. Abstract: As plastic waste accumulates in the ocean at alarming rates, the need for efficient and sustainable remediation solutions is urgent. One solution is the development and mobilization of technologies that either 1) prevent plastics from entering waterways or 2) collect marine and riverine plastic pollution. To date, however, few reports have focused on these technologies, and information on various technological developments is scattered. This leaves policymakers, innovators, and researchers without a central, comprehensive, and reliable source of information on the status of available technology to target this global problem. The goal of this study was to address this gap by creating a comprehensive inventory of technologies currently used or in development to prevent the leakage of plastic pollution or collect existing plastic pollution. Our Plastic Pollution Prevention and Collection Technology Inventory (https://nicholasinstitute.duke.edu/plastics-technology-inventory ) can be used as a roadmap for researchers and governments to 1) facilitate comparisons between the scope of solutions and the breadth and severity of the plastic pollution problem and 2) assist in identifying strengths and weaknesses of current technological approaches. We created this inventory from a systematic search and review of resources that identified technologies. Technologies were organized by the type of technology and target plastics ( i.e., macroplastics, microplastic, or both). We identified 52 technologies that fall into the two categories of prevention or collection of plastic pollution. Of these, 59% focus specifically on collecting macroplastic waste already in waterways. While these efforts to collect plastic pollution are laudable, their current capacity and widespread implementation are limited in comparison to their potential and the vast extent of the plastic pollution problem. Similarly, few technologies attempt to prevent plastic pollution leakage, and those that do are limited in scope. A comprehensive approach is needed that combines technology, policymaking, and advocacy to prevent further plastic pollution and the subsequent damage to aquatic ecosystems and human health.